Modeling the effects of prebiotic interventions on luminal and mucosa-associated gut microbiota without and with Clostridium difficile challenge in vitro - Wiese, Maria; van der Wurff, Michelle; Ouwens, Anita; van Leijden, Bowien; Verheij, Elwin R.; Heerikhuisen, Margreet; van der Vossen, Jos M. B. M. (Frontiers in Nutrition, 2024)
Prebiotics can modulate the gut microbial community composition and function for improved (gut) health and increase resilience against infections. In vitro models of the gut facilitate the study of intervention effects on the gut microbial community relevant to health. The mucosa-associated gut microbiota, which thrives in close contact with the host plays a pivotal role in colonization resistance and health. Therefore, we here introduce the Mi-screen, an experimental approach implementing a 96well-plate equipped with a mucus agar layer for the additional culturing of a mucosa-associated microbiota in vitro. In this study, we screened the effects of 2'-Fucosyllactose (2'-FL), fructooligosaccharides (FOS), and inulin within a complex microbiota without and with infection with the C. difficile strains ATCC 43599 (Ribotype 001) or ATCC BAA-1870 (Ribotype 027). We analyzed the microbial community composition and short-chain fatty acid levels after 48 hours of incubation. The inclusion of an additional substrate and surface in the form of the mucus agar layer allowed us to culture a microbial diversity ranging between 110-150 in Chao index, with Shannon indices of 5-6 across culture conditions, indicative of a microbial diversity of physiological relevance. The mucus agar layer stimulated the growth of characteristic mucosa-associated bacteria such as Roseburia inulinovorans. The prebiotic interventions affected luminal and mucosal microbial communities cultured in vitro and stimulated acetic, propionic, and butyric acid production. FOS and inulin promoted the growth of Bifidobacterium adolescentis within the mucosa-associated microbiota cultured in vitro. When spiking the untreated conditions with pathogenic C. difficile, the strains thrived within the luminal and the mucosal sample types, whereas prebiotic treatments exhibited inhibitory effects on C. difficile growth and prevented colonization. In conclusion, the Mi-screen facilitates the screening of luminal and mucosa-associated gut microbial community dynamics in vitro and therefore fills an important gap in the field of in vitro modeling.